Zimbabwe : Staff Report for the 2012 Article IV Consultation - Cuevas, Alfredo (IMF Staff Country Reports; Country Report ;, 2012)
Under Article IV of the IMF's Articles of Agreement, the IMF holds bilateral discussions with members, usually every year. In the context of the 2012 Article IV consultation with Zimbabwe, the following documents have been released and are included in this package.